Effect of piperlongumine during exposure to cigarette smoke reduces inflammation and lung injury - Sant'Ana, Monielle; Souza, Helena R. [UNESP]; Possebon, Lucas [UNESP]; Cornélio, Marinônio L. [UNESP]; Riffo-Vasquez, Yanira; Girol, Ana Paula [UNESP]; Oliani, Sonia M. [UNESP] (Elsevier, 2020)
Chronic obstructive pulmonary disease (COPD) is related to smoking and anti-inflammatory therapy is indicated. Among the mediators with anti-inflammatory properties, we highlight piperlongumine (PL), an alkaloid/amide of Piper longum. Here we evaluated the PL administration on an experimental model of respiratory inflammation resulting from exposure to cigarette smoke. Male Balb/c mice were exposed to burning of 10 commercial cigarettes, 2x/day, for five weeks on specific equipment. PL efficacy was evaluated in control, exposed to smoke without treatment and PL treated (2.0 mg/kg, 3x/week) groups. Animals were weighed and plethysmographic analyses performed at the end of the exposure protocol. Inflammatory cells were evaluated in the bronchoalveolar lavage (BAL) and hemoglobin and glucose in the blood. Lung fragments were processed for histopathological studies and AnxA1, COX-2, NF-kB and neutrophil elastase expressions. Plethysmography revealed that PL maintained pulmonary frequency, volume and ventilation parameters similar to controls, with respiratory volume reduction compared to untreated animals. Final weight was reduced in both exposed groups. PL decreased hemoglobin concentration, attenuated the reduction of glucose levels and reduced influx of lymphocytes, neutrophils and macrophages in BAL. Histopathologically occured infiltration of inflammatory cells, increase of the interalveolar septa and intra-alveolar spaces in untreated animals. But, PL administration recovered lung tissues and, immunohistochemically, promoted increased expression of AnxA1 and reduction of COX-2, NF-kB and neutrophil elastase. Together the results indicate that PL attenuates systemic and pulmonary inflammatory changes, partially by modulating the expression the endogenous AnxA1, and may represent a promising therapy in preventing the inflammation induced by cigarette smoke.
Keywords: Annexin A1; Bronchoalveolar lavage; Chronic obstructive pulmonary disease; Inflammatory cells; Mice; Smoking